Syndemics & syndemogenesis in COVID-19 and rheumatic and musculoskeletal diseases: old challenges, new era. (26th January 2021) - Nikiphorou, Elena; Alpizar-Rodriguez, Deshire; Gastelum-Strozzi, Alfonso; Buch, Maya; Peláez-Ballestas, Ingris
Abstract: People with rheumatic and musculoskeletal diseases (RMDs) are facing several challenges during the COVID-19 pandemic, such as poor access to regular health services and drug shortages, particularly in developing countries. COVID-19 represents a syndemic, synergistic condition that interacts with and exacerbates pre-existing diseases such as RMDs, other co-morbidities and social conditions. The emerging evidence on both biological and non-biological factors implicated in worse outcomes in people with RMDs affected by the COVID-19 pandemic, whether infected by the virus or not, calls for the need to use more novel and holistic frameworks for studying disease. In this context, the use of a syndemic framework becomes particularly relevant. We appeal for a focus on the identification of barriers and facilitators to optimal care of RMDs in the context of the COVID-19 pandemic, in order to tackle both the pandemic itself and the health inequities inherent to it.